The Hospitality Marketing Mix development guidelines towards Tourists needs : Mae Sai Pa Meing Village, Long Khod Sub-district, Prao District, Chiang Mai Province - ยาวิราช, ศิริรักษ์; สุวรรณเสรีรักษ์, ชรัญญา; ศรีจันทร, เก็จวลี; อินฝาง, ศุภวัชร์; สุขมณี, รุจิรา (Community and Social Development Journal, 2018)
This research aimed to study the development hospitality marketing mix for the needs of tourists in Mae Sai Pa Meing, Long Khod Sub-district ,Prao District, Chiang Mai Province. The qualitative data were collected by group interview from 10 samples . The male samples were 3 and female samples were 7. The experimental was the travel program for 2 days 1 night. The samples were divided into 2 groups: 1) The group will return to the place and 2) The group is uncertain to return to the place or will not come back to the place . The main factors which make the samples return to the place are people. They shared the same opinion about the friendliness and helpfulness of people. The other factors are beautiful products, the abundance of nature ,good culture, the traditional way of living and physical presentation which is clean. It is an important selling point if it has been updated to be more convenient and safety. In addition, standardized processes, fast, communication and convenient distribution channels will help to promote Mae Sai Pa Meing to be well known more quickly.